Psycho-Trauma, Psychosocial Adjustment, and Symptomatic Post-Traumatic Stress Disorder among Internally Displaced Persons in Kaduna, Northwestern Nigeria - Sheikh, Taiwo Lateef; Mohammed, Abdulaziz; Agunbiade, Samuel; Ike, Joseph; Ebiti, William N.; Adekeye, Oluwatosin (Frontiers in Psychiatry, 2014)
Background In April 2011, a post election violent conflict in Northern Nigeria led to resettlement of internally displaced persons (IDPs) in a camp in Kaduna, the worst affected state. We set out to determine prevalence and socio-demographic factors associated with post-traumatic stress disorder (PTSD) among IDPs. We also determined types of psycho-trauma experienced by the IDPs and their psychosocial adjustment. Methods Cross-sectional systematic random sampling was used to select 258 adults IDPs. We used Harvard trauma questionnaire to diagnose “symptomatic PTSD”, composite international diagnostic interview for diagnosis of depression, and communal trauma event inventory to determine exposure to psycho-trauma. We assessed social adjustment using social provision scale. Multiple logistic regression was used to determine independent predictors of PTSD. Results Of the 258 IDPs, 109 (42.2%) had a diagnosis of PTSD, 204 (79.1%) had poor living conditions, and only12 (4.7%) had poor social provision. The most frequent psycho-traumas were destruction of personal property (96.1%), been evacuated from their town (96%) and witnessing violence (88%). More than half (58%) of IDPs had experienced 11 – 15 of the 19 traumatic events. Independent predictors of PTSD among respondents were, having a CIDI diagnosis of depression (Adjusted Odd Ratio [AOR]3.5, 95% CI 1.7 – 7.5; p= 0.001) and witnessing death of a family member ( 3.7, 1.2 – 11.5; p=0.0259). Conclusion We concluded that exposure to psycho-trauma among IDPs in Kaduna led to post conflict PTSD. Death of a family member and co-morbid depression were independent predictors of PTSD among IDPs. Though their living condition was poor, the IDPs had good psychosocial adjustment. We recommended a structured psychosocial intervention among the IDP targeted at improving living condition and dealing with the psychological consequences of psycho-trauma. Key words Post traumatic stress disorder, psychosocial adjustment, psycho-